Development of a Problem Based Learning Student Worksheet on the Hydrocarbon Topic for Grade XI Students - Akhmad Syafiq Razan; Effendi Nawawi (Global Action and Education for Society, 2025)
This development research aims to produce a Problem-Based Learning (PBL)-based Student Worksheet on Hydrocarbon material that is valid, practical, and effective. The research method used was Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate), combined with the Tessmer evaluation model. Data were collected using validation sheets, student response questionnaires, and conceptual understanding tests. Expert validation results indicate that the worksheet meets the very valid criteria with Aiken's V scores of 0.92 (subject expert), 0.96 (design expert), and 0.90 (pedagogical expert). In the practicality test involving 9 grade XI students, the worksheet achieved a practicality percentage of 98.4% (very practical category). Furthermore, the effectiveness test, measured by the N-gain score, resulted in a value of 0.8, which is categorized as high. It is concluded that the developed PBL-based worksheet has been proven to meet the criteria of being valid, practical, and effective for use in learning Hydrocarbon material.